Interactive effect of trivalent iron on activated sludge digestion and biofilm structure in attached growth reactor of waste tire rubber. Issue 2 (17th January 2018) - Sharafat, Iqra; Saeed, Dania Khalid; Yasmin, Sumera; Imran, Asma; Zafar, Zargona; Hameed, Abdul; Ali, Naeem
ABSTRACT: Waste tire rubber (WTR) has been introduced as an alternative, novel media for biofilm development in several experimental systems including attached growth bioreactors. In this context, four laboratory-scale static batch bioreactors containing WTR as a support material for biofilm development were run under anoxic condition for 90 days using waste activated sludge as an inoculum under the influence of different concentrations (2.5, 6.5, 8.5 mg/l) of trivalent ferric iron (Fe 3+ ). The data revealed that activated sludge with a Fe 3+ concentration of 8.5 mg/l supported the maximum bacterial biomass [4.73E + 10 CFU/ml cm 2 ]; besides, it removed 38% more Chemical oxygen demand compared to Fe 3+ free condition from the reactor. Biochemical testing and 16S rDNA phylogenetic analysis of WTR-derived biofilm communities further suggested the role of varying concentrations of Fe 3+ on the density and diversity of members of Enterobacteria(ceae), ammonium (AOB) and nitrite oxidizing bacteria. Furthermore, Fluorescent in situ hybridization with phylogenetic oligonucleotide probes and confocal laser scanning microscopy of WTR biofilms indicated a significant increase in density of eubacteria (3.00E + 01 to.05E + 02 cells/cm 2 ) and beta proteobacteria (8.10E + 01 to 1.42E + 02 cells/cm 2 ), respectively, with an increase in Fe 3+ concentration in the reactors, whereas, the cell density of gamma proteobacteria in biofilms decreased.